A typical manifestation of conjunctival epithelial inclusion cyst - Jinagal, Jitender; Gupta, Parul Chawla; Kakkar, Nandita; Ram, Jagat (Nepalese Journal of Ophthalmology, 2018)
Purpose: To report a case of conjunctival epithelial inclusion cyst with atypical manifestation.Methods: A 26-year-old male presented with a blackish-brown, subconjunctival mass located in palpebral conjunctiva of the upper eyelid. En bloc excision of the mass was performed and evaluated on histopathological examination.Results: The excised mass was well defined, dark brown in colour and simulated a solid foreign body. On histopathological examination, the mass was lined by stratified squamous epithelium with florid hyperkeratosis and haemorrhage inside it, consistent with atypical conjunctival epithelial inclusion cyst.Conclusion: A careful clinical examination and histopathological study is essential for the differential diagnosis of subconjunctival mass as rarely they may present with atypical manifestations.